Genetic and Immunological Profiling of Recent SARS-CoV-2 Omicron Subvariants: Insights into Immune Evasion and Infectivity in Monoinfections and Coinfections - Nadine Alvarez; Irene Gonzalez-Jimenez; Risha Rasheed; Kira Goldgirsh; Steven Park; David S. Perlin (Viruses)
The evolution of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and its impact on public health continue to demand attention as the virus continues to evolve, demonstrating a remarkable ability to adapt to diverse selective pressures including immune responses, therapeutic treatments, and prophylactic interventions. The SARS-CoV-2 variant landscape remains dynamic, with new subvariants continuously emerging, many harboring spike protein mutations linked to immune evasion. In this study, we characterized a panel of live SARS-CoV-2 strains, including those key subvariants implicated in recent waves of infection. Our findings revealed a significant variability in mutation patterns in the spike protein across the strains analyzed. Commercial antibodies and human convalescent plasma (HCoP) samples from unvaccinated donors were ineffective in neutralizing the most recent Omicron subvariants, particularly after the emergence of JN.1 subvariant. Using human airway epithelial cells derived from healthy bronchiolar tissue (hBAEC), we established both monoinfections and coinfections involving SARS-CoV-2, Influenza A virus H1N1 (IFAV_H1N1) and Respiratory Syncytial Virus (RSV). Assessments were conducted to compare viral infectivity and the production and release of immune mediators in the apical and basolateral compartments. Notably, Omicron KP.3.1.1 subvariant induced a more pronounced cytopathic effect in hBAEC compared to its parental strain JN.1 and even surpassed the impact observed with the ancestral wild-type virus (WA1/2020, Washington strain). Furthermore, the coinfection of KP.3.1.1 subvariant with IFAV_H1N1 or RSV did not attenuate SARS-CoV-2 infectivity; instead, it significantly exacerbated the pathogenic synergy in the lung epithelium. Our study demonstrated that pro-inflammatory cytokines IL-6, IFN-β, and IL-10 were upregulated in hBAEC following SARS-CoV-2 monoinfection with recent Omicron subvariants as well as during coinfection with IFAV_H1N1 and RSV. Taken together, our findings offer new insights into the immune evasion strategies and pathogenic potential of evolving SARS-CoV-2 Omicron subvariants, as well as their interactions with other respiratory viruses, carrying important implications for therapeutic development and public health preparedness.